Tuning the morphologies of SiC nanowires via the change of the CoxSiy melts - Chen, J. J.; Pan, Y.; Tang, W. H.; Shi, Q. (Nano-Micro Letters, 2010)
SiC nanowires and SiC/SiO2 core-shell structural nanowires were synthesized via a simple thermal evaporation of CoxSiy melts at the temperature of 1500°C. The morphologies and yields of those SiC nanowires can be tuned by altering the composition of CoxSiy. Nanowires obtained by thermal evaporation of CoSi are composed of SiC/SiO2 core-shell nanostructures with lengths up to several hundreds of micrometers, diameters of 40∼50 nm, and the thickness of amorphous SiO2 wrapping shell about 20 nm. SiC nanowires prepared by thermal evaporation of CoSi2 and Co2Si melt are found to be hexagonal-prism-shaped nanorods, and the diameter of those nanorods is about 150 nm and the length is about 10 microns. All the SiC nanowires obtained possess [111] preferred growth direction with a high density stacking faults and twin defects. Taking into consideration the binary alloy diagram of CoSi and the participation of oxygen, we propose the vapor-solid growth mechanism of SiC nanowires and discuss the effect of the supersaturation of SiO on the morphology and yields of SiC nanowires.